2018
DOI: 10.1080/09593985.2018.1453569
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hip extensor muscle activity including the adductor magnus during three prone hip extension exercises

Abstract: Based on these results, we advocate including the Amag as a hip extensor during the PHE test or exercise. Our preliminary results have the potential to be applied directly to the PHE test, for investigating the muscle-activation pattern of the Amag with the Gmax and hamstrings in patients with hip or lower back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…However, most of the therapeutic exercises can activate AM at a high (41-60%MVIC) to a very high (>60%MVIC) level. Han-i Ko and colleagues found that AM can be strengthened from 44±26.5% MVIC to 86.2±46.9% MVIC in active prone hip extension with hip adduction or abduction [24]. Another study evaluated the EMG of AM in six clinical examination tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of the therapeutic exercises can activate AM at a high (41-60%MVIC) to a very high (>60%MVIC) level. Han-i Ko and colleagues found that AM can be strengthened from 44±26.5% MVIC to 86.2±46.9% MVIC in active prone hip extension with hip adduction or abduction [24]. Another study evaluated the EMG of AM in six clinical examination tests.…”
Section: Discussionmentioning
confidence: 99%
“…The provided sample size was 16. Therefore, we recruited 20 healthy volunteers (7 males and 13 females, aged [20][21][22][23][24][25][26][27][28][29][30] to participate in the study. All subjects were fully informed of the procedures and purposes of this study and provided written informed consent.…”
Section: Introductionmentioning
confidence: 99%
“…Its most important role is in hip extension. Weakness of GM increases the stress on the intervertebral disc and lumbar spine ligaments [6,14,15]. Trunk and lumbo-pelvic exercises instantaneously increase the activities of erector spinae (ES) and hamstring muscles to compensate for the hip extension movement [5,9,16].…”
Section: Introductionmentioning
confidence: 99%
“…Also, previous studies have found significant differences in muscle activities between prone hip extension (PHE) and PHE-adduction and PHE-abduction exercises. The PHE-abduction position more increases the GM muscle activity than PHE [14]. Additionally, Jeon et al [20] measured the activities of ES, GM, biceps femoris (BF), and semitendinosus (ST) muscles during three hip extension exercises.…”
Section: Introductionmentioning
confidence: 99%